Endotracheal N-acetylcysteine for Atelectasis in Neonatal Pneumonia - Mustafa Dilek; Halil İbrahim Atasoy; Seher Açar (Galenos Yayinevi, 2019)
Although there is no gold standard therapy in the treatment of atelectasis in newborns, surfactant therapy, inhaled mucolytic agents, recombinant human deoxyribonuclease, positive pressure mechanical ventilation, postural changes and drainage can be used. However, N-acetylcysteine (NAC), via endo-bronchoscopy, is rarely used to break the disulfide bonds in the mucus. It is a cheap and readily available treatment to apply. Here, we present a newborn with neonatal pneumonia to whom we instilled NAC thorough an endotracheal tube to resolve right lung total atelectasis. The atelectasis responded to instillation quickly and successfully. We are presenting this case in order to suggest a novel effective treatment modality for already intubated newborns with atelectasis. This case also represents the first successful treatment case in the newborn period.